The Machine Has a Soul 2021
DOI: 10.23943/princeton/9780691208107.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Garden of Fascism

Abstract: This chapter addresses how American fascist sympathizers used Italo Balbo's 1933 North Atlantic flight to insist on the peaceful intentions of Benito Mussolini's regime. While it had been easy for most Americans to agree with fascist sympathizers' characterizations of Italo Balbo in July of 1933, the claims that Italy represented beauty, transcendence, and peace felt more farfetched as the decade progressed. Balbo alighted in Chicago only a few months after Adolf Hitler assumed dictatorial powers in Germany. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Their interpretation has drawn primarily on Italian Americans’ efforts to avoid the imposing of limits on exports to Mussolini's regime at the time of the Ethiopian War as well as on their endeavors to back that colonial venture financially. Specifically, John Norman (1949), Brice Harris (1964: 122−125), John P Diggins (1972: 302−306), Leo V Kanawada (1982: 81−89), Gian Giacomo Migone (1980: 343−357), Fiorello B Ventresco (1980), Nadia Venturini (1990: 119−165), Matteo Pretelli (2010: 68−71; 2022: 162−163), Stanislao G Pugliese (2017: 353−354, 356), Valeria Federici (2018), Katy Hull (2021: 141−143), Chiara Grilli (2021), and Jessica H Lee (2022a: 206–208)—among others—have shown that Italian Americans contributed hundreds of thousands of dollars to the Duce's war chest, albeit disguised as humanitarian funds for the Italian Red Cross, donated their wedding rings and other gold objects to fascism in protest against the economic sanctions of the League of Nations, and exploited the forthcoming 1936 Congressional elections to threaten not to vote for Senators and Representatives who would help pass the Pittman-McReynolds Bill, restricting the shipment of US oil, trucks, and scrap iron to Italy for the duration of the military conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Their interpretation has drawn primarily on Italian Americans’ efforts to avoid the imposing of limits on exports to Mussolini's regime at the time of the Ethiopian War as well as on their endeavors to back that colonial venture financially. Specifically, John Norman (1949), Brice Harris (1964: 122−125), John P Diggins (1972: 302−306), Leo V Kanawada (1982: 81−89), Gian Giacomo Migone (1980: 343−357), Fiorello B Ventresco (1980), Nadia Venturini (1990: 119−165), Matteo Pretelli (2010: 68−71; 2022: 162−163), Stanislao G Pugliese (2017: 353−354, 356), Valeria Federici (2018), Katy Hull (2021: 141−143), Chiara Grilli (2021), and Jessica H Lee (2022a: 206–208)—among others—have shown that Italian Americans contributed hundreds of thousands of dollars to the Duce's war chest, albeit disguised as humanitarian funds for the Italian Red Cross, donated their wedding rings and other gold objects to fascism in protest against the economic sanctions of the League of Nations, and exploited the forthcoming 1936 Congressional elections to threaten not to vote for Senators and Representatives who would help pass the Pittman-McReynolds Bill, restricting the shipment of US oil, trucks, and scrap iron to Italy for the duration of the military conflict.…”
Section: Introductionmentioning
confidence: 99%